Make money as a buyer’s agent : - Howell-Carey, Chantal (John Wiley & Sons, 2007)
Traditionally, real estate agents help home sellers get the best deal on their home, but no one covers the buyer’s side. This guide shows you how to make the switch from representing sellers to representing buyers, so you can keep making money even as the seller’s market slows down. Learn to earn big commissions, no matter what happens to the market.